Penegakan Hukum Terhadap Pelaku Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial - Zakiya, Zahra; Cannavaro, Fabio; Pangestu, Sultan Dwi; Ilham, Ilham; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The rapid development of digital technology and social media has contributed to the increasing number of defamation cases in Indonesia. This study aims to analyze law enforcement against perpetrators of defamation through social media based on the Electronic Information and Transactions Law (UU ITE). The research employs a literature review method, examining legislation, government reports, police data, and academic publications. Data indicate a significant rise in reported defamation cases, increasing from 320 cases in 2019 to 760 cases in 2024, based on compiled data from the Indonesian Cyber Crime Directorate and supporting sources. The findings reveal several challenges in law enforcement, particularly concerning proof of “intent” and “harmful impact,” as well as interpretational ambiguity within Article 27 paragraph (3) of the UU ITE. Additionally, the rapid dissemination of information on social media amplifies the impact of defamation. This study highlights the need to improve regulations, strengthen digital literacy, and enhance the capacity of law enforcement officers to ensure fair and proportional law enforcement.